CHRDL2 promotes osteosarcoma cell proliferation and metastasis through the BMP‐9/PI3K/AKT pathway. (5th January 2021) - Chen, Houping; Pan, Runsang; Li, Hao; Zhang, Wenguang; Ren, Chong; Lu, Qiaoying; Chen, Hui; Zhang, Xiangyan; Nie, Yingjie
Abstract: Various studies demonstrated that bone morphogenetic proteins (BMPs) and their antagonists contribute to the development of cancers. Chordin‐like 2 (CHRDL2) is a member of BMP antagonists. However, the role and its relative mechanism of CHRDL2 in osteosarcoma remains unclear. In the present study, we demonstrated that the expression of CHRDL2 was significantly upregulated in osteosarcoma tissues and cell lines compared with adjacent tissues and human normal osteoblast. Inhibition of CHRDL2 decreased the proliferation and colony formation of osteosarcoma cells in vitro, as well as the migration and invasion. CHRDL2 overexpression induced the opposite effects. CHRDL2 can bind with BMP‐9, thus decreasing BMP‐9 expression and the combination to its receptor protein kinase ALK1. It was predicted that BMP‐9 regulates PI3K/AKT pathways using gene set enrichment analysis. Inhibition of CHRDL2 decreased the activation of PI3K/AKT pathway, while overexpression of CHRDL2 upregulated the activation. Increasing the expression of BMP‐9 reversed the effects of CHRDL2 overexpression on the activation of PI3K/AKT pathway, as well as the proliferation and metastasis of osteosarcoma cells. Take together, our present study revealed that CHRDL2 upregulated in osteosarcoma tissues and cell lines, and promoted osteosarcoma cell proliferation and metastasis through the BMP‐9/PI3K/AKT pathway. CHRDL2 maybe an oncogene in osteosarcoma, as well as novel biomarker for the diagnosis of osteosarcoma.